Numerical Modelling of Slope Stability and Transient Seepage Analysis: Jalan Puncak Borneo Road Case Study - Awang Ismail, D. S.; Taib, S. N. L.; Sa’don, N. M. (International Journal of Integrated Engineering, 2023)
A slope failure event in 2015 at KM 6+500 of Jalan Puncak Borneo in Padawan, Kuching was modelled using Seep/w and Slope/w software of commercial geotechnical programme GEOSTUDIO. The failure was occurred after a prolonged three days of heavy rain. The state road which connected the villagers from Puncak Borneo was cut off and caused traffic congestion.  In this study, the slope stability was evaluated based on finite element and limit equilibrium method by considering the transient seepage analysis due to rainfall infiltration.  The slope failure was modelled based on ground investigation report and published data to replicate the field condition.  A hyetograph was plotted using daily rainfall data and cumulative rainfall depth was determined to obtain the total rainfall during the wet monsoon. As a result of numerical analyses, the factor of safety was observed to fluctuate with time of infiltration. Based on this case study, the factor of safety or FOS reduced with time and a perched water table also has been observed developed just below the pavement.  However, the factor of safety calculated from Slope/w could not replicate the actual failure.  Nevertheless, it can be observed that factor of safety had decreased with respect to infiltration in the analyses.  The steady state condition provided FOS 1.33 and had reduced to 1.27 after 110 days of rainfall event.  Thus, the analyses of this current study have illustrated that the transient analysis is essential to model the seepage behaviour and infiltration event that caused slope failure along Sarawak’s roads.